Pipelines 2017. proceedings of sessions of the Pipelines 2017 Conference, August 6-9, 2017, Phoenix, Arizona - Pridmore, Anna B.; Geisbush, Jim (American Society of Civil Engineers, 2017)
"This collection contains 57 peer-reviewed papers on geomatics, surveying and condition assessment of pipelines for reliability and resiliency through sustainable design and construction. Topics include: contingency planning; GIS and alternative project delivery; construction and rehabilitation; large diameter projects; design-build alternative delivery; distribution transmission; emerging technologies; and case studies."--